KEMAMPUAN ADSORBSI ABU SEKAM PADI TERHADAP AIR DAN ASAM LEMAK BEBAS VIRGIN COCONUT OIL (VCO) DALAM KOLOM ADSORBSI - Laras mariance sulo; Khairuddin; Ruslan (KOVALEN: Jurnal Riset Kimia, 2019)
A research has been conducted on the adsorption ability of rice husk ash to water content and free fatty acid of virgin coconut oil (VCO) in the adsorption column. The objective of this research is to get the ratio of coarse VCO to rice husk ash adsorbent in the column that produces VCO with water content, free fatty acid that meets SNI and yields VCO yield not less than 80%. This study used a completely randomized factorial design (CRF design) with the effect of the amount of rice husk ash adsorbent (5g, 10g, 15g, 20g, 25g) in in columns 2.5 and 3 inches. The result of research on column 2.5 inch of the lowest water content (0.2%) was found on the weight of rice husk ash 25g and free fatty acid content on 25g ash husk ash was 0.1%. And at column 3.0 inch the lowest water content was found on 25g ash husk ash 0.1%, and the lowest free fatty acid content on ash weight of rice husk 25g was 0.2% and the best yield was 90%. Keywords: free fatty acid, rice husk ash adsorbent, moisture content, Virgin Coconut Oil